2006
DOI: 10.2307/20445365
|View full text |Cite
|
Sign up to set email alerts
|

Phonetic: Semantic Mediated False Recognition: Does Activation Fail to Spread?

Abstract: Spoken word recognition involves brief activation of candidate words. Six experiments examined whether words semantically related to phonologically activated words would be falsely recognized. Experiments 1 and 2 involved homophones as test words; Experiment 3 used strong associates for the semantic mediation link. Experiment 4 approximated lists of "strong" converging associates. Experiment 5 expanded the real time needed for word identification by using a gating procedure during study. In Experiment 6, the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…A recent series of experiments failed to demonstrate phonetic-semantic mediation effects in false recognition. Based on phonetic/orthographic similarity, early in the processing of a studied word such as hamster, words similar in sound and appearance (e.g., ham, hamburger, hammer) may be activated; however, data indicated that activation of hammer during the initial stages of processing hamster did not lead to an increase in false recognitions to the critical lure ''nail'' (Wallace, Salapska-Gelleri, Belz, & Owen, 2006). In the case of nonword study items such as dearm, if ''dream'' is activated (either through misperception or recoding), its semantic associates should have relatively few semantic competitors that would be directly elicited by the nonword dearm.…”
Section: Differences Between False Recognition Proportions For Criticmentioning
confidence: 98%
“…A recent series of experiments failed to demonstrate phonetic-semantic mediation effects in false recognition. Based on phonetic/orthographic similarity, early in the processing of a studied word such as hamster, words similar in sound and appearance (e.g., ham, hamburger, hammer) may be activated; however, data indicated that activation of hammer during the initial stages of processing hamster did not lead to an increase in false recognitions to the critical lure ''nail'' (Wallace, Salapska-Gelleri, Belz, & Owen, 2006). In the case of nonword study items such as dearm, if ''dream'' is activated (either through misperception or recoding), its semantic associates should have relatively few semantic competitors that would be directly elicited by the nonword dearm.…”
Section: Differences Between False Recognition Proportions For Criticmentioning
confidence: 98%